EFFECT OF MULTI MICRONUTRIENT SUPPLEMENTATION ON HEMOGLOBIN LEVELS IN PREGNANT WOMEN WITH ANEMIA - Rati Purnama Sari; Noor Pramono; Sri Wahyuni; Muchlis Achsan Udji Sofro; Melyana Nurul Widyawati (Belitung Raya Foundation, 2017)
Background: The coverage of 90 Fe tablets in Semarang in 2015 was 26.619 of 29.490 pregnant women (97%) but the incidence of anemia in pregnant women was still quite high. One important factor which influences the levels of hemoglobin is multi micronutrient. Objective: This study aims to analyze the changes in hemoglobin levels with multi micronutrient supplementation in pregnant women with anemia. Methods: A Quasy experimental study with randomized control group pre-post test design. The study samples were 40 pregnant women with gestational age of 20 ± 1 weeks divided into two groups, the intervention group (multi micronutrient supplementation) and the control group (Fe supplementation) for 6 weeks. The study was conducted from November 2016 to January 2017. The levels of hemoglobin were measured using cyanmethohemoglobin. Paired t test and independent t test were used for data analyses. Results: The mean increase in hemoglobin levels after multi micronutrient supplementation was 1.545 (1.292) g/dl, whereas the mean increase in hemoglobin levels after Fe supplementation was 0.757 (0.742) g/dl. The difference in hemoglobin levels before and after multi micronutrient supplementation was significantly different (p=0.049). Cohen's d effect size test showed value of 0.748. Conclusion: Multi micronutrient supplementation could improve hemoglobin levels. Increase in the levels of hemoglobin with multi micronutrient supplementation was higher than Fe supplementation.